Kamma and the Buddhist Hell - Rui Han (Religions)
As an extension of the Problem of Evil, the Problem of Hell poses further difficulties for the theodicy and eschatology of Western theist religions. This Problem of Hell, which presumes a transcendent divine entity, is, however, less applicable to an Eastern religious tradition like Buddhism. As a non-theist religion, Buddhism is not centered on an overpowering God but is predicated on the doctrine of kamma. Hell in Buddhism is conceived as one of the rebirth realms in the saṃsāra where beings are driven to by the force of their kamma. This kamma-based conception of hell has its own unique features, especially with regard to retribution and salvation. It also has a unique problem. As the doctrine of kamma is commonly understood as an endorsement of free will, it appears to conflict with another Buddhist doctrine, namely that of dependent origination, which is often interpreted as suggesting a deterministic worldview. This tension between doctrines of kamma and dependent origination is also known as the Buddhist free will problem, as it involves the controversy over the metaphysics of free will. Based on the Pāli scriptures, the essay tries to propose a compatibilist solution to the problem, defending kamma for the Buddhist hell.